VISUAL BASIC 6.0 APPLICATION FOR ADMISSION BOOKING SYSTEM IN PT. ABC - Nugroho Budi Santoso; Lingga Hermanto, SSi, MMSi (Jurnal Sistem Informasi, 2003)
Writing is about problems that arise in the ticket reservation system. The author proposes an application to solve these problems while improving the quality of the service ticket reservation system.With this application we can find out quickly who is still an empty seat so as to speed the process of ticket reservation services. Attached to the end writing programs to support the application.